Impact of stress hyperglycemia ratio on incidence of in-hospital cardiogenic shock in patients with ST-elevation myocardial infarction: a prospective, multicenter study - Wang, Shan; Zhang, You; Yang, Wei; Wang, Xianpei; Zhu, Zhongyu; Qi, Datun; Zhang, Jing; Zhang, Jian; Gao, Chuanyu (Frontiers in Endocrinology, 2025)
BackgroundThe stress hyperglycemia ratio (SHR) has emerged as a valuable prognostic indicator in patients with ST-elevation myocardial infarction (STEMI). Nevertheless, the impact of SHR on the incidence of in-hospital cardiogenic shock (IHCS) remains insufficiently explored in patients with STEMI. This study aimed to investigate the association between SHR and IHCS incidence while assessing its additional predictive value beyond established risk scores.MethodsData were derived from a prospective, multicenter registry and included 1776 patients with STEMI. Patients were grouped by the optimal cutoff value of SHR. The primary endpoint was the incidence of IHCS. Generalized linear mixed models, restricted cubic splines (RCS), ROC curves, and decision curve analysis (DCA) were utilized, with feature importance assessing its importance.ResultsThe IHCS incidence was notably higher in patients with elevated SHR. RCS analysis indicated a significant dose-response relationship between increasing SHR and IHCS risk (P-Nonlinear > 0.05). SHR was independently associated with IHCS in the overall population (OR: 2.19, 95% CI: 1.20-4.00) and in patients without diabetes (OR: 2.20, 95% CI: 1.11-4.35). Incorporating SHR into established risk scores significantly improved predictive accuracy and net clinical benefit. SHR was comparably important in predicting IHCS compared to established risk factors.ConclusionsElevated SHR is a valuable predictor and manifests additional predictive value beyond established risk scores in predicting IHCS in patients with STEMI, especially among patients without diabetes.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT02641262.